1998
DOI: 10.1093/ps/77.3.405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yeast-supplemented feed on Salmonella and Campylobacter populations in broilers

Abstract: The effect of the yeast, Saccharomyces boulardii, on experimental cecal colonization of broilers with Salmonella typhimurium and Campylobacter jejuni was investigated. Duplicate pens of broiler chicks were given ad libitum access to a standard feed supplemented with no yeast (control), or 1 g (1x), or 100 g (100x) dried S. boulardii/kg feed. All chicks except negative controls were challenged on Day 4 with 3.2 x 10(8) cfu S. typhimurium and 6.5 x 10(8) cfu C. jejuni by oral gavage. After 3 wk, the broilers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
7

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 20 publications
1
63
0
7
Order By: Relevance
“…In a study by Sadiaa et al (2010) results show that adding live yeast at 0.4 or 0.8% into laying hen diets can enhance the productive performance and nutrients utilization via the inhibitory effect of yeast against pathogenic bacteria also reveals that probiotics could be successfully used as nutritional tools in poultry feeds for promotion of growth, modulation of intestinal microflora and pathogen inhibition, immunomodulation and promoting meat quality of poultry (Saadia and Nagla, 2010). The antagonistic effect of live yeast against intestinal microflora was elucidated by Line et al (1998) that, several harmful pathogenic bacteria have been shown to exhibit a binding specific for the sugar mannose. A live yeast cells contain mannose in their wall.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Sadiaa et al (2010) results show that adding live yeast at 0.4 or 0.8% into laying hen diets can enhance the productive performance and nutrients utilization via the inhibitory effect of yeast against pathogenic bacteria also reveals that probiotics could be successfully used as nutritional tools in poultry feeds for promotion of growth, modulation of intestinal microflora and pathogen inhibition, immunomodulation and promoting meat quality of poultry (Saadia and Nagla, 2010). The antagonistic effect of live yeast against intestinal microflora was elucidated by Line et al (1998) that, several harmful pathogenic bacteria have been shown to exhibit a binding specific for the sugar mannose. A live yeast cells contain mannose in their wall.…”
Section: Resultsmentioning
confidence: 99%
“…This mannose in the cell wall may cause the yeast to act as a decoy for the attachment of pathogens. Results have shown that yeast does not permanently colonize animals, the yeast and any yeast-bound pathogens are passed out in the bird excretion and bacterial colonization is diminished (Line et al, 1998). Kabir et al (2004) reported that probiotic microorganisms, once established in the gut, may produce substances with bactericidal or bacteriostatic properties (bacteriocins) such as lactoferrin, lysozyme, hydrogen peroxide as well as several organic acids.…”
Section: Resultsmentioning
confidence: 99%
“…and coliforms in the feces during phases I, II and III (Table 6). It has been reported that dietary sources of protein and fermentable carbohydrates affect the host animal by improving its intestinal balance (Fuller, 1989) and creating gut micro-ecological conditions that suppress harmful microorganisms such as Clostridium and coliforms (Line et al, 1998;Pascual et al, 1999;Shim et al, 2010), as well as by favoring beneficial microorganisms like Lactobacillus and Bifidobacterium. In the present experiment, there were no differences in microflora populations among pigs fed diets containing SBM of different origin.…”
Section: Fecal Microfloramentioning
confidence: 99%
“…and coliforms in the excreta during starter and finisher period. It has reported that dietary sources of fermentable carbohydrates and protein affect the host animal by improving its intestinal balance (Fuller, 1989) and creating gut micro-ecological conditions that suppress harmful microorganisms like Clostridium and Coliforms (Line et al, 1998;Pascual et al, 1999;Shim et al, 2010), and by favoring beneficial microorganisms like Lactobacillus and Bifidobacterium. In the present experiment, there were no differences in microbial population among birds fed diets containing SBM from different origin.…”
Section: Microbial Populationsmentioning
confidence: 99%